2014
DOI: 10.1515/epoly-2014-0163
|View full text |Cite
|
Sign up to set email alerts
|

UV-curable electromagnetic shielding composite films produced through waterborne polyurethane-acrylate bonded graphene oxide: preparation and effect of different diluents on the properties

Abstract: UV-curable electromagnetic shielding composite films (UV-EMSF) were prepared with graphene oxide/polyurethane-acrylate (GO-PUA) oligomers, different diluents (styrene-butyl acrylate or tripropyleneglycol diacrylate-butyl acrylate or trimethylol propane triacrylate-butyl acrylate) and photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone). The chemical structures, morphology, crystallinity and thermal behavior of UV-EMSF were investigated by Fourier transform-infrared spectroscopy, scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The incorporation of inorganic nanoparticles into a UV-WPU matrix is an effective strategy to enhance some properties and provide specific functionalities to this system [152]. Hardness, tensile strength, water absorption, solvent resistance, and thermal behavior of UV-WPUs can be significantly improved by adding nanoparticles like acryloyl chloride modified lysozyme [134], silver [90,157], graphene oxide [107,112,113], surfactant-modified TiO 2 /reduced graphene oxide [45], graphitic carbon nitride [94], and Fe 3 O 4 [70,71]. These nanoparticles also provide excellent antibacterial activity, electrical conductivity, good electronic stability, self-cleaning ability in photocatalysis, and unique magnetic behavior to the coatings.…”
Section: Nanoparticles As a Reinforcement Componentmentioning
confidence: 99%
“…The incorporation of inorganic nanoparticles into a UV-WPU matrix is an effective strategy to enhance some properties and provide specific functionalities to this system [152]. Hardness, tensile strength, water absorption, solvent resistance, and thermal behavior of UV-WPUs can be significantly improved by adding nanoparticles like acryloyl chloride modified lysozyme [134], silver [90,157], graphene oxide [107,112,113], surfactant-modified TiO 2 /reduced graphene oxide [45], graphitic carbon nitride [94], and Fe 3 O 4 [70,71]. These nanoparticles also provide excellent antibacterial activity, electrical conductivity, good electronic stability, self-cleaning ability in photocatalysis, and unique magnetic behavior to the coatings.…”
Section: Nanoparticles As a Reinforcement Componentmentioning
confidence: 99%
“…APUAD modified with graphene oxide were also recently studied [80,81] and it was found that just 0.015 % of that nanofiller was sufficient to obtain much improved water resistance of the film while higher amounts were not as effective in that regard. Other nanofillers -nano ZnO and superparamagnetic iron oxide (SPIO) were also used for modification of APUD [71,82] and nanosilver was used for modification of 2-component waterborne polyurethane based on water-dispersible polyol -water-dispersible polyisocyanate system [83].…”
Section: Aqueous Polyurethane and Polyurethane-acrylic Dispersions Comentioning
confidence: 99%